Effects of the carbonization temperature and intermediate cooling mode on the properties of coal-based activated carbon. (15th June 2023) - Zhao, Can; Ge, Lichao; Li, Xi; Zuo, Mingjin; Xu, Chunyao; Chen, Simo; Li, Qian; Wang, Yang; Xu, Chang
Abstract: To optimize the production of coal-based activated carbon, the effects of carbonization temperature on the surface functional groups, crystal characteristics, degree of graphitization, thermal stability and mechanical strength of char were studied; additionally, the effects of intermediate cooling on the pore structure, adsorption capacity and mechanical strength of activated carbon were studied. The results showed that the raw material lost many functional groups during carbonization. Carbonization improved the degree of graphitization, thermal stability and mechanical strength of the raw material, and char with a high degree of graphitization, a high thermal stability and mechanical strength was obtained with a higher carbonization temperature. The activated carbon prepared by direct heating after carbonization had a more developed pore structure, adsorption capacity and mechanical strength. The pore structure of the activated carbon was mainly produced during activation. Finally, the optimal conditions were determined as follows: a carbonization temperature of 800 °C and direct heating for activation after carbonization. The yield of the activated carbon was 48.2%, the Brunauer–Emmett–Teller specific surface area was 494 m 2 ∙g −1, the total pore volume was 0.29 cm 3 ∙g −1, the iodine value was 785 mg∙g −1, the compressive strength was 23.5 daN, and the wear strength was 83.5%. Graphical abstract: Image 1 Highlights: Carbonization improved the thermal stability and mechanical strength. Activation further developed the pore structure of the char. Higher temperatures enhanced the thermal stability and mechanical strength. Intermediate cooling influenced the yield and mechanical strength. Activation enhanced the adsorption capacity but weakened the mechanical strength.